(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Thyroidectomy, the second most common endocrine surgical procedure after diabetes-related surgery, carries significant risk of injury to the recurrent laryngeal nerve (RLN) and parathyroid glands, which can result in permanent dysphonia or hypocalcaemia. Intraoperative methylene blue spray exploits the avascular Schwann sheath of the RLN rendering it unstained and the dense lymphovascular supply of parathyroid glands that enables rapid dye uptake and washout, offering a simple, low-cost adjunct for safe thyroid surgery. Aim: To evaluate the utility and safety of intraoperative methylene blue spray in identifying the RLN and parathyroid glands during thyroidectomy. Materials and Methods: A prospective observational study was conducted on 35 patients undergoing thyroidectomy at HSK Hospital between September 2023 and September 2025. After superior pole ligation, 1 ml of 1% methylene blue solution was sprayed over the thyroid lobe and perithyroidal area. Pre- and post-operative indirect laryngoscopy was performed and serum calcium levels were measured. Statistical analysis used paired t-test and chi-square test; p < 0.05 was significant. Results: The study included 35 patients (88.6% female, 11.4% male). Both the RLN and parathyroid glands were successfully identified in 91.4% (n=32) of cases; in 8.6% (n=3), the RLN was identifiable but parathyroid identification was unsuccessful. The RLN remained unstained in 100% of cases. Post-operative indirect laryngoscopy confirmed normal vocal cord mobility in all 35 patients, with no RLN palsy. A statistically significant post-operative decline in serum calcium was noted (8.88 ± 0.46 vs. 8.36 ± 0.59 mg/dL; p < 0.001); however, no patient developed clinical hypocalcaemia. No adverse effects attributable to methylene blue were recorded. Conclusion: Intraoperative methylene blue spray is a safe, simple, inexpensive, and effective technique for identification of the RLN and parathyroid glands during thyroidectomy. It is a valuable adjunct to safe thyroid surgery, particularly where intraoperative neuromonitoring is unavailable.